(untitled) (Economic and Political Thought, 2012)
The article aims to analyze the European Union diplomacy, i.e. the European External Action Service (EEAS), which was created based on the decisions of the Treaty of Lisbon. The article presents such issues as the theoretical difference between foreign policy and diplomacy, which are often confused in journalistic texts, the origin of the EU’s foreign service, and the definition of its character and basic tasks. The article also contains a discussion of the role the EEAS plays in the Common Security and Defence Policy. The article also deals with the EEAS inter-institutional location, which is very important from the point of view of its daily functioning. The article ends with some deliberations in connection with the role of the High Representative for Foreign Affairs and Security Policy as well as the role of the member states in the current functioning of the European External Action Service.